ANALISIS PENGENDALIAN INTERN ATAS PERSEDIAAN BARANG DAGANG PADA CV. MITA JAYA KOTA BENGKULU - Azuwandri, Azuwandri; Yusnita, Yuli; Novrianda, Herry (Jurnal Adminitrasi Bisnis Nusantara, 2024)
Inventory is a very important asset for trading and industry companies because it is a source of revenue for the company. Inventory is very adamant to damage and crime, therefore it is necessary internal control of inventory. Therefore, the purpose of this study is to find out how the application of internal control of merchandise inventory on the CV. Mita Jaya. In this writing, the method of analysis used is descriptive analysis method. Data collection methods used in this paper is to make direct observation, interviews and literature study by studying reference books and similar previous research results to get the theoretical basis of the problem to be studied. The result of this research is internal control system on inventory at CV. Mita Jaya includes procedures for purchasing / ordering merchandise, sales procedures and procedures for receipt of merchandise. In the application of this internal control there are several parties responsible for monitoring and overseeing the process of transactions related to merchandise inventory.